D-Lactic acid production by Sporolactobacillus inulinus YBS1-5 with simultaneous utilization of cottonseed meal and corncob residue. (May 2016) - Bai, Zhongzhong; Gao, Zhen; Sun, Junfei; Wu, Bin; He, Bingfang
Graphical abstract: Highlights: S. inulinus YBS1-5 had low nutrient requirement ford -lactic acid production. Efficientd -lactic acid production from cheap cottonseed meal was demonstrated. Corncob residue was suitable ford -lactic acid fermentation by strain YBS1-5. A combined use produced 107.2 g/Ld -lactic acid with a yield of 0.85 g/g. Abstract: d -Lactic acid, is an important organic acid produced from agro-industrial wastes by Sporolactobacillus inulinus YBS1-5 was investigated to reduce the raw material cost of fermentation. The YBS1-5 strain could produced -lactic acid by using cottonseed meal as the sole nitrogen source. For efficient utilization, the cottonseed meal was enzymatically hydrolyzed and simultaneously utilized duringd -lactic acid fermentation. Corncob residues are rich in cellulose and can be enzymatically hydrolyzed without pretreatment. The hydrolysate of this lignocellulosic waste could be utilized by strain YBS1-5 as a carbon source ford -lactic acid production. Under optimal conditions, a highd -lactic acid concentration (107.2 g/L) was obtained in 7-L fed-batch fermenter, with an average productivity of 1.19 g/L/h and a yield of 0.85 g/g glucose. The optical purity ofd -lactic acid in the broth was 99.2%. This study presented a new approach for low-cost production ofd -lactic acid for an industrial application.